Antioxidant activity of Rosa damascene flos ethanol extracts using hydroxyl and nitrite oxide scavenging methods - T, Elfina Br; G, Chrismis N; C, Linda; L, I Nyoman E (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: The purpose of this study were to determine antioxidant activity of Rosa damascene flos ethanol extracts. Methods: The ethanol extracts were extracted from the crown of rose and rose base by maceration using ethanol 70% solvent. Antioxidant activity was determined with hydroxyl and nitrite oxide scavenging methods and the IC50analyzed using SPSS 23. Results: The IC50of crown rose ethanol extract (CREE) and rose base ethanol extract (RBEE) on hydroxyl and nitrite oxide scavenging were7.61 ± 0.38μg/mL, 17.55 ± 0.37 μg/mL and were 349,57 ±0,35μg/mL, 54.93 ± 4.49 μg/mL. Conclusions: The crown of rose ethanol extract (CREE) and rose base ethanol extract (RBEE) has activity as antioxidant.